1625-27 Washington Street, ca. 1910 - Unknown (Tufts Archival Research Center, 2005)
Street-level view north-northwest (left to right) of 1625-27 Washington Street, located between West Concord Street to the southwest and Rutland Street to the northeast. Signage and awnings adorn the facades of the buildings, which face southeast. Three men pose in front of a Boston Ice Company cart on Washington Street. Copyprint (original in private collection of donor, Glenn Kelley) 4 3/4 x 6 1/2, 5 1/8 x 6 3/4 overall Photographs